Optimizing the Management and Outcomes of Failed Back Surgery Syndrome: A Proposal of a Standardized Multidisciplinary Team Care Pathway - Kliment Gatzinsky; Sam Eldabe; Jean-Philippe Deneuville; Wim Duyvendak; Nicolas Naiditch; Jean-Pierre Van Buyten; Philippe Rigoard (Pain Research and Management)
Failed back surgery syndrome (FBSS) is a major, worldwide health problem that generates considerable expense for healthcare systems. A number of controversial issues concerning the management of FBSS are regularly debated, but no clear consensus has been reached. This pitfall is the result of lack of a standardized care pathway due to insufficient characterization of underlying pathophysiological mechanisms, which are essential to identify in order to offer appropriate treatment, and the paucity of evidence of treatment outcomes. In an attempt to address the challenges and barriers in the clinical management of FBSS, an international panel of physicians with a special interest in FBSS established the Chronic Back and Leg Pain (CBLP) Network with the primary intention to provide recommendations through consensus on how to optimize outcomes. In the first of a series of two papers, a definition of FBSS was delineated with specification of criteria for patient assessment and identification of appropriate evaluation tools in order to choose the right treatment options. In this second paper, we present a proposal of a standardized care pathway aiming to guide clinicians in their decision-making on how to optimize their management of FBSS patients. The utilization of a multidisciplinary approach is emphasized to ensure that care is provided in a uniform manner to reduce variation in practice and improve patient outcomes.